Doping dependent electronic and magnetic ordering in mixed-valent La1−x Sr x MnO3 thin films - J A Payne; C T Bryant; R Marquez Tavera; D T Brown; T M Pekarek; M P Warusawithana (Materials Research Express, 2022)
We have investigated the collective electronic and magnetic orderings of a series of La _1− _x Sr _x MnO _3 thin films grown epitaxially strained to (001) oriented strontium titanate substrates as a function of doping, x , for 0 ≤ x ≤ 0.4. We find that the ground states of these crystalline thin films are, in general, consistent with that observed in bulk crystals and thin film samples synthesized under a multitude of techniques. Our systematic study, however, reveal subtle features in the temperature dependent electronic transport and magnetization measurements, which presumably arise due to Jahn-Teller type distortions in the lattice for particular doping levels. For the parent compound LaMnO _3 ( x = 0), we report evidence of a strain-induced ferromagnetic ordering in contrast to the antiferromagnetic ground state found in bulk crystals.